Antioxidant Activity Test of Salak Bali Peel Extract (Salacca zalacca var. amboinensis) Against Brain Cells of Male Mice (Mus musculus L.) Induced by Alloxan - Padmiswari, Anak Agung Istri Mas; Wulansari, Nadya Treesna; Harditya, Kadek Buja; Megayanti, Sri Dewi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This study aims to test the antioxidant activity of salak Bali peel extract (Salacca zalacca var. amboinensis) against brain cells of male mice (Mus musculus L.) exposed to alloxan. Free radicals can trigger damage to brain cells through oxidative mechanisms, which contribute to the development of various neurodegenerative diseases that can damage cells in the body. Salak Bali peel extract contains bioactive compounds such as flavonoids, tannins, and polyphenols that are antioxidant-active. This study was conducted using a completely randomized design (CRD) in mice induced by alloxan at a dose of 150 mg/kg BW (group 1), followed by oral administration of salak Bali peel extract at a dose of 4.2 mg/kg BW (group 2) and 8.4 mg/kg BW (group 3) for 35 days. The control group used in this study was alloxan, which was used to compare the treatment results with conditions without intervention so that the effects of the treatment could be identified more clearly. The results of the antioxidant analysis test using the DPPH method showed an IC50 value of the salak Bali peel extract of 45.5 µg/mL, indicating a high antioxidant capacity. Histopathological analysis revealed that administration of salak Bali peel extract could reduce necrosis in the brain tissue of mice induced by alloxan, suggesting a neuroprotective effect. Therefore, salak Bali peel extract has the potential to be a source of natural antioxidants that can be used to prevent brain damage due to oxidative stress and as a therapy for treating neurodegenerative diseases.